Menyoal Validitas Sadd Al-Dharai‘ sebagai Dalil Hukum Islam: Polemik Epistemologis Ushuliyyin: Questioning the Validity of Sadd Al-Dharai' as an Islamic Legal Argument: Ushuliyyin Epistemological Polemics - Sansan Ziaul Haq (Institut Agama Islam Negeri Fattahul Muluk Papua, 2024)
This paper will discuss the discourse of sadd al-dharai‘ as an evidence of Islamic law along with various epistemological perspectives that underlie the differences of opinion regarding its jurisprudential position. Using the content analysis method and normative-philosophical approach, a qualitative reading of the research data shows that the polemic of ushuliyyin regarding the validity of sadd al-dharai‘ is caused by differences of opinion regarding whether or not it is permissible to judge haram an act that is permissible but can lead to haram based on strong suspicion (dzann). Meanwhile, if this act leads to haram with certainty (bi-al-qat‘i) or with great possibility (ghalabat al-dzann), then almost all the ‘Ulama agree that it is forbidden. This finding strengthens the assumption of the reliability of sadd al-dharai‘ as an Islamic legal argument, because it emphasizes the material-objective aspect of what happens in the field, not the intention of the actor which is difficult to measure definitely. However, further studies are needed to examine the reliability of this legal argument in providing positive and contextual solutions to various contemporary issues.